2016
DOI: 10.3390/ijms17081242
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anti-Epileptic Drugs on Growth and Bone Metabolism

Abstract: Epilepsy is a common neurological disorder worldwide and anti-epileptic drugs (AEDs) are always the first choice for treatment. However, more than 50% of patients with epilepsy who take AEDs have reported bone abnormalities. Cytochrome P450 (CYP450) isoenzymes are induced by AEDs, especially the classical AEDs, such as benzodiazepines (BZDs), carbamazepine (CBZ), phenytoin (PT), phenobarbital (PB), and valproic acid (VPA). The induction of CYP450 isoenzymes may cause vitamin D deficiency, hypocalcemia, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 194 publications
(243 reference statements)
0
70
1
2
Order By: Relevance
“…As early as 2004, it was reported that several factors affect bone metabolism in children with epilepsy, suggesting that long-term use of AEDs may cause damage to the skeletal system [5]. Cytochrome P450 (CYP450) isozyme can be induced by AEDs such as carbamazepine, phenytoin sodium, phenobarbital and valproic acid, which may lead to vitamin D deficiency, hypocalcemia, increased fracture risk [6]. Opinions suggest that long-term use of this drug may have an impact on bone metabolism in children [1][2][3]7].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 2004, it was reported that several factors affect bone metabolism in children with epilepsy, suggesting that long-term use of AEDs may cause damage to the skeletal system [5]. Cytochrome P450 (CYP450) isozyme can be induced by AEDs such as carbamazepine, phenytoin sodium, phenobarbital and valproic acid, which may lead to vitamin D deficiency, hypocalcemia, increased fracture risk [6]. Opinions suggest that long-term use of this drug may have an impact on bone metabolism in children [1][2][3]7].…”
Section: Introductionmentioning
confidence: 99%
“…; despite having 27.3% of their treated group taking two or more anticonvulsants [20]. On the other hand, several studies have looked at associations between anticonvulsant use and BMD [31][32][33], with most studies conducted primarily in patients with epilepsy and in paediatric populations [15]. It has been estimated that over 50% of anticonvulsant users develop bone anomalies [31], and studies conducted over time have shown that long-term use is associated with increased fracture risk and associated bone disease [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have looked at associations between anticonvulsant use and BMD [31][32][33], with most studies conducted primarily in patients with epilepsy and in paediatric populations [15]. It has been estimated that over 50% of anticonvulsant users develop bone anomalies [31], and studies conducted over time have shown that long-term use is associated with increased fracture risk and associated bone disease [32,34]. In a large, multiethnic, postmenopausal cohort (n = 138,667, aged 50-79 years), anticonvulsant use was associated with an increased fracture risk, which was further increased with polypharmacy and enzyme-inducing anticonvulsants rather than the non-enzyme inducing type [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the conventional AEDs, early reports have focused on inducers of cytochrome P450 (CYP) enzyme such as carbamazepine, phenobarbital, phenytoin and primidone that can activate the PXR, increasing vitamin D metabolism and eventually leading to hypocalcemia and secondary hyperparathyroidism (113). In a total of 600 patients receiving AEDs, 45% had 25(OH)D level <20 ng/mL while deficiency was present in 54% of enzyme-inducing and 37% of non-enzyme-inducing antiepileptic drug groups (114).…”
Section: Antiepileptic Drugsmentioning
confidence: 99%